Language formation by adults : the case of Sino-Russian idiolects - Frajzyngier, Zygmunt; Gurian, Natalia; Karpenko, Sergeĭ (Brill Studies in language contact and dynamics of language ;, 2021)
"Chinese immigrants who settle in Russia's Far East without formal instruction in the Russian language communicate with local Russians using Russian vocabulary. Each immigrant forms their language to communicate with Russians, not with family or other immigrants. The 'single-generation languages' that immigrants form are not replications or simplifications of Chinese or Russian. Grammatical systems formed by these speakers challenge some fundamental assumptions in early 21st-century linguistic theories. Grammatical systems of single-generation languages provide a unique window into how complex grammatical systems emerge, what are the first formal means of expression, and what are the first meanings expressed in grammatical systems. Given massive migrations in the contemporary world, single-generation languages are common, yet understudied, products of language contact"--